2019
DOI: 10.1016/j.soilbio.2019.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Drought-induced decline of productivity in the dominant grassland species Lolium perenne L. depends on soil type and prevailing climatic conditions

Abstract: Severe constraints on grasslands productivity, ecosystem functions, goods and services are expected to result from projected warming and drought scenarios under climate change. Negative effects on vegetation can be mediated via soil fertility and water holding capacity, though specific mechanisms are fairly complex to generalise. In field drought experiments, it can be difficult to disentangle a drought effect per se from potential confounding effects related to vegetation or soil type, both varying along with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…These authors also showed that heat waves in summer were indirectly increasing the negative effect of drought on biomass production decrease. At both of our study sites, air temperatures were higher, and induced higher vapour-pressure deficit (VPD), during the late-season drought compared to the early-season drought (VPD = 0.78 vs. 0.47 KPa at Site 1 and VPD = 0.59 vs. 0.27 KPa at Site 2; see Buttler et al . 2019).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…These authors also showed that heat waves in summer were indirectly increasing the negative effect of drought on biomass production decrease. At both of our study sites, air temperatures were higher, and induced higher vapour-pressure deficit (VPD), during the late-season drought compared to the early-season drought (VPD = 0.78 vs. 0.47 KPa at Site 1 and VPD = 0.59 vs. 0.27 KPa at Site 2; see Buttler et al . 2019).…”
Section: Discussionmentioning
confidence: 79%
“…plant growing season, 6 months, see Fig. 1) was 441 ± 36 mm at Site 1 and 682 ± 46 mm at Site 2, and mean daily average temperatures were 16 ± 0.3 °C at Site 1 and 13.5 ± 0.3 °C at Site 2 (see also Buttler et al 2019). Despite receiving different amount of precipitation during the plant growing season, both sites experience similar rainfall frequency with about 11 rainy days per months with precipitation equally spread over the season (see Buttler et al 2019).…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…Therefore, it remains unclear whether a three-cut regime would still outperform the four-cut regime in the long term. This is especially relevant because an increased frequency of extreme weather events such as droughts and heavy rain is projected for European grassland areas [61][62][63][64][65] and therefore their management needs to become less intensive with regard to cutting frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…Based on modelled predictions, grassland productivity could be enhanced under future climate, i.e., rising temperatures and potentially longer cropping seasons [7]. However, reduced soil water availability in summer may also limit the growing season [8], reducing forage productivity and increasing the variability of yield [9]. In the short-term in England and Wales, Rounsevell et al [10] predicted that climate change was unlikely to have a negative impact on grasslands, although, across Europe, the impact of climate change is likely to vary significantly between regions [11,12].…”
Section: Introductionmentioning
confidence: 99%